Supervision of the Pelalawan Regency Environmental Service on Palm Oil Industry Waste in Langgam District - Syaprianto, Syaprianto (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2022)
The Environmental Agency has the task of supervising hazardous and toxic waste (B3). This office ensures that B3 waste management meets applicable environmental standards and does not harm the environment and public health. This study aims to determine the implementation of supervision carried out by the Pelalawan Regency Environmental Service on industrial waste management in Langgam District and to find out the inhibiting factors of the Environmental Service in conducting supervision. This research uses qualitative methods in which data is collected through observation, interviews, and documentation. Informants in this study are considered able to answer research problems, and the object of research is whether oil palm companies carry out waste management. The results showed that in carrying out the Supervision of the Pelalawan Regency Environmental Service was considered to have been carried out but not maximized; this was evidenced by the still occurring river pollution carried out by oil palm companies in Pangkalan Gondai Village, Pelalawan District. The pollution disrupts community activities, and the community cannot consume river water. The obstacles experienced by the Pelalawan Regency Environmental Service in supervising hazardous waste management are the limited number of employees who are competent in monitoring industrial waste in quality and quantity. Furthermore, the limited budget owned by the Office considering a large number of companies and the need for more awareness of business actors or companies in following B3 waste management regulations